El impuesto predial y su impacto en las finanzas públicas - Acosta Bermedo, Otto Alonso (2013)
Public finance is of much importance for the sustainability of a State. For that purpose,there are diverse tax mechanisms that are key to achieve that purpose, such as the case of Property Taxes. However, can we affirm that this tax achieves that goal in Peru? Is the rate properly fixed? Is there an adequate administration and recollection of taxes? In this investigation, TH?MIS studies the diverse challenges that come up in fiscal decentralization in this country, showing off a legal perspective as well. It also brings a dynamic study of Property Taxes, concluding that it has a very decisive impact on public finance, and for that reason, the rate must be progressively modified and increased. It will be fundamental that the recollection may be done with good governance that allows both the decentralization and maximization of the funds use, in order to benefit all sectors.